Implementação de IPv6 na rede do câmpus Curitiba da UTFPR: um estudo de caso - Carvalho, Bruno Tokarski de (2020)
The evolution of computer networks has formed what is called Internet: a big network of networks. The basis of communication on the Internet is a protocol developed in the sixties that, with minor modifications, operates today on a worldwide scale as the communication standard for all connected services. IPv4 is this protocol and one of the main deficits of this version is the size of the addresses, which directly impacts the quantity available. To remedy this problem, IPv6 was developed which, among other improvements to the old protocol, greatly increases the number of available addresses. As the new version of the protocol is not directly compatible with the old one, the existing computer networks will have to migrate to the new protocol só that the Internet can continue its expansion without limitations caused by the lack of addresses. This work analyzes the implementation of the IPv6 protocol in dual stack in the UTFPR Câmpus Curitiba network.